2003
DOI: 10.1111/j.1348-0421.2003.tb03377.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lactobacillus rhamnosus on Enterohemorrhagic Escherichia coli Infection of Human Intestinal Cells In Vitro

Abstract: There are many examples of probiotic effects of various lactic bacteria on enteropathogens. In this study, Lactobacillus strains (L. rhamnosus, L. gasseri, L. casei and L. plantarum) were tested in an in vitro model of enterohemorrhagic Escherichia coli (EHEC) infection of a human colon epithelial cell line, C2BBe1. While the adhesion and colonization of EHEC was not affected by any of the lactobacillus strains tested, the internalization of EHEC into the cell line was markedly suppressed by L. rhamnosus, thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 21 publications
(12 reference statements)
1
49
2
1
Order By: Relevance
“…Several reports have confirmed the ability of probiotic Lactobacilli to inhibit the ability of pathogenic bacteria to adhere to and to invade intestinal epithelial cells (4,10,20,26,27). The inhibition levels observed with L. casei DN-114 001 are similar to or even higher than those reported for Lactobacilli on the adhesion of various pathogens (4,11,18,20,49).…”
Section: Discussionmentioning
confidence: 95%
“…Several reports have confirmed the ability of probiotic Lactobacilli to inhibit the ability of pathogenic bacteria to adhere to and to invade intestinal epithelial cells (4,10,20,26,27). The inhibition levels observed with L. casei DN-114 001 are similar to or even higher than those reported for Lactobacilli on the adhesion of various pathogens (4,11,18,20,49).…”
Section: Discussionmentioning
confidence: 95%
“…Previous work has shown, for example, that E. coli O157:H7 binds to the surfaces of S. boulardii cells (9). On the other hand, Hirano and coworkers (12) reported that L. rhamnosus blocks the internalization, but not the adherence, of E. coli O157:H7 in Caco-2 cells. Other lactic acid-producing bacteria, including Lactobacillus gasseri, Lactobacillus casei, and Lactobacillus plantarum, have no effect on either the binding or internalization of E. coli O157:H7 in Caco-2 cell monolayers (12).…”
mentioning
confidence: 97%
“…On the other hand, Hirano and coworkers (12) reported that L. rhamnosus blocks the internalization, but not the adherence, of E. coli O157:H7 in Caco-2 cells. Other lactic acid-producing bacteria, including Lactobacillus gasseri, Lactobacillus casei, and Lactobacillus plantarum, have no effect on either the binding or internalization of E. coli O157:H7 in Caco-2 cell monolayers (12). This study shows that L. rhamnosus and L. acidophilus have the ability to adhere to host epithelial cells and reduce the binding of both E. coli O157:H7 and E. coli E2348/69 to host epithelial cells.…”
mentioning
confidence: 97%
“…The findings point to the possible role of SH compounds in the protective effect of some probiotics [72]. Lactobacillus GG significantly suppresses internalization of enterohemorrhagic E. coli in tissue culture [34,73]. This effect is mediated by high adhesivity of the probiotic to colonocytes and by MUC-3 gene activation with subsequent mucus secretion [74].…”
Section: Experimental Colitis and Enterocolitismentioning
confidence: 92%